THE WAYS OF NATURAL REGENERATION OF OAK STANDS IN THE WESTERN FOREST-STEPPE OF UKRAINE - Kopiy, Leonid; Kopiy, Serhiy; Lentiakov, Volodymyr; Chaplyk , Olga (Forestry, Forest, Paper and Woodworking Industry, 2024)
The present paper deals with the analysis of silvicultural treatment effects on fruiting, emergence of common oak advance regeneration, the dynamics of its mortality, changes in mycological structure, and re-distribution of nutrients across the soil profile. The peculiarities of common oak advance regeneration were investigated at the experimental sections of various thinning intensity. The study has revealed the relationship between the sunlight intensity and changes in biometrical indices of oak advance regeneration.